Treatment of tuberculosis under the view of the user - Ana Angélica Lima Dias; Daniela Maria Falcão de Oliveira; Ellen Cristine Ramdohr Sobrinho; Pedro Fredemir Palha; Rosely Moralez de Figueiredo (Universidade Federal do Ceará, 2014)
Clinical-qualitative study aimed at analyzing the experiences of users who completed treatment for tuberculosis in the county of São Carlos-São Paulo, Brazil. Data were collected from February to September 2011, through semi-structured interviews, with 15 users. These were organized according to the content analysis technique, thematic modality. The patients face difficulties in being diagnosed and use different health services; they suffer with the reactions resulting from the treatment, and the supervision of drug intake is seen both as a facilitator for the formation of the link and also as a deterrent to adherence. Assessment researches related to difficulty in establishing the diagnosis and the monitoring of the supervised treatment should be made to minimize the barriers to control the disease.